Chemical Composition of Natural Hydrolates and Their Antimicrobial Activity on Arcobacter-Like Cells in Comparison with Other Microorganisms - Šilha, David; Švarcová, Karolína; Bajer, Tomáš; Královec, Karel; Tesařová, Eliška; Moučková, Kristýna; Pejchalová, Marcela; Bajerová, Petra (My University, 2020)
Hydrolates obtained via the hydrodistillation and steam distillation of Lavandula angustifolia Mill., Syzygium aromaticum L., Foeniculum vulgare Mill., and Laurus nobilis L. were analyzed by gas chromatography with flame ionization detector (GC-FID) and gas chromatography coupled to mass spectrometry (GC-MS). Additionally, the hydrolates were evaluated for antimicrobial activity (disk-diffusion and microdilution method), influence on biofilm formation (Christensen method) and cytotoxicity of concentrated hydrolates against human cell lines (A549) by xCELLigence system. Using chemical analysis, 48, 9, 13 and 33 different components were detected in lavender, clove, fennel and laurel hydrolates, respectively. Lavender hydrolate contained the largest proportion of 1,8-cineol, linalool furanoxide, and linalool. The main components of laurel hydrolate were 1,8-cineol, 4-terpineol and α-terpineol. Fenchone and estragole were the most abundant in fennel hydrolate, and eugenol and eugenyl acetate in clove hydrolate. Concentrated hydrolates showed significant antimicrobial activity. Clove hydrolate was among the most antimicrobially active agents, most preferably against C. albicans, with an inhibition zone up to 23.5 mm. Moreover, concentrated hydrolates did not show any cytotoxic effect again8 st human A549 cells. In the presence of the non-concentrated hydrolates, significantly reduced biofilm formation was observed; however, with concentrated clove hydrolate, there was an increase in biofilm formation, e.g., of A. thereius, A. lanthieri, and A. butzleri. Research shows new findings about hydrolates that may be important in natural medicine or for preservation purposes.
Chemické složení přírodních hydrolátů a jejich antimikrobiální activita na Arcobacter-like buňky ve srovnání s dalšími mikroorganismy
Keywords: Lavandula angustifolia; Syzygium aromaticum; Foeniculum vulgare; Laurus nobilis; hydrolates; distillation; Arcobacter-like bacteria; antimicrobial activity; biofilm formation; gas chromatography; Lavandula angustifolia; Syzygium aromaticum; Foeniculum vulgare; Laurus nobilis; hydroláty; destilace; Arcobacter-like; antimikrobiální aktivita; tvorba biofimů; plynová chromatografie